slr2103, a homolog of type-2 diacylglycerol acyltransferase genes, for plastoquinone-related neutral lipid synthesis and NaCl-stress acclimatization in a cyanobacterium, Synechocystis sp. PCC 6803 - Kondo, Mimari; Aoki, Motohide; Hirai, Kazuho; Sagami, Taku; Ito, Ryo; Tsuzuki, Mikio; Sato, Norihiro (Frontiers in Plant Science, 2023)
A cyanobacterium, Synechocystis sp. PCC 6803, contains a lipid with triacylglycerol-like TLC mobility but its identity and physiological roles remain unknown. Here, on ESI-positive LC-MS2 analysis, it is shown that the triacylglycerol-like lipid (lipid X) is related to plastoquinone and can be grouped into two subclasses, Xa and Xb, the latter of which is esterified by 16:0 and 18:0. This study further shows that a Synechocystis homolog of type-2 diacylglycerol acyltransferase genes, slr2103, is essential for lipid X synthesis: lipid X disappears in a Synechocystis slr2103-disruptant whereas it appears in an slr2103-overexpressing transformant (OE) of Synechococcus elongatus PCC 7942 that intrinsically lacks lipid X. The slr2103 disruption causes Synechocystis cells to accumulate plastoquinone-C at an abnormally high level whereas slr2103 overexpression in Synechococcus causes the cells to almost completely lose it. It is thus deduced that slr2103 encodes a novel acyltransferase that esterifies 16:0 or 18:0 with plastoquinone-C for the synthesis of lipid Xb. Characterization of the slr2103-disruptant in Synechocystis shows that slr2103 contributes to sedimented-cell growth in a static culture, and to bloom-like structure formation and its expansion by promoting cell aggregation and floatation upon imposition of saline stress (0.3-0.6 M NaCl). These observations provide a basis for elucidation of the molecular mechanism of a novel cyanobacterial strategy to acclimatize to saline stress, and one for development of a system of seawater-utilization and economical harvesting of cyanobacterial cells with high-value added compounds, or blooming control of toxic cyanobacteria.